PENGEMBANGAN MODEL BIMBINGAN KELOMPOK BERBASIS NILAI KARAKTER LOKAL JAWA UNTUK MENINGKATKAN KESADARAN DIRI (SELF AWARENESS) SISWA. - Dewi, Novianti Kartika (Jurnal Counsellia, 2013)
Self-awareness is the ability of individuals to think of themselves not only as an actor of environmental, but also as an object attention of the others. Based on the preliminary data the researcher found if the level of self-awareness Junior High Schoolâs student divided into 3 categories, there are high 38.3%, moderate 40%Â  and lower 21.7%. Given the importance of self-awareness to be owned by all the students, so it is need necessary to relief efforts to increase self-awareness of the students. Which ones effort to help the students increase their self-awareness is optimize the implementation of guidance group services. Model of guidance group based on the value of java local characters can be used as an alternative to maximize the quality of guidance services.Keywords: model of guidance group based on the values of java local characters, self-awareness students.Kesadaran diri adalahÂ  kemampuan individu untuk memikirkan dirinya bukan hanya sebagai aktor lingkungan, namun juga sebagai objek perhatian orang lain. Bedasarkan studi pendahuluan ditemukan bahwa tingkat kesadaran diri siwa SMP berada pada kategori tinggi 38,3%, sedang 40% dan rendah 21,7 %. Mengingat pentingnya kesadaran diri untuk dimiliki oleh semua siswa maka perlu adanya upaya bantuan untuk meningkatkan kesadaran diri siswa tersebut. Adapun upaya yang perlu dilakukan untuk membantu siswa meningkatkan kesadaran diri (self awareness) adalah dengan mengoptimalkan pelaksanaan layanan bimbingan kelompok. Model bimbingan kelompok berbasis nilai karakter lokal jawa ini dapat dijadikan sebagai salah satu alternatif dalam memaksimalkan mutu layanan bimbingan kelompok.Kata kunci: model bimbingan kelompok berbasis nilai karakter lokal jawa, kesadaran diri (self awareness) siswa.